2016
DOI: 10.1007/s10803-016-2887-1
|View full text |Cite
|
Sign up to set email alerts
|

A Group-Administered social Skills Training for 8- to 12- Year-Old, high-Functioning Children With Autism Spectrum Disorders: An Evaluation of its Effectiveness in a Naturalistic Outpatient Treatment Setting

Abstract: A social skills training (SST) for high-functioning children with autism spectrum disorders (ASD) was evaluated in an outpatient setting using a combined between- and within-subject design in which SST and a waiting list condition were compared. According to parents and teachers, the SST produced greater improvement of social skills than the waiting list, and these effects were maintained at 3 months follow-up. No between-group effects were found for loneliness, although in general scores on this outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
(54 reference statements)
3
23
0
1
Order By: Relevance
“…Interventions that enhance social skills might be of great value. In fact, it has been demonstrated that social skills training for children with ASD can successfully decrease feelings of loneliness [ 60 ]. It is recommended to implement this type of intervention before the transition from primary to secondary school so that children are better equipped to face the social challenges of adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions that enhance social skills might be of great value. In fact, it has been demonstrated that social skills training for children with ASD can successfully decrease feelings of loneliness [ 60 ]. It is recommended to implement this type of intervention before the transition from primary to secondary school so that children are better equipped to face the social challenges of adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…These findings seem to fit with the picture that youths with ASD, especially during the adolescent years when they experience at least some desire for social interaction, often fail to realize satisfactory social interactions resulting in feelings of loneliness [ 17 , 25 ]. This also suggests that social skills training might be particularly valuable in terms of intervention [ 60 ]. That is, by increasing the social abilities of young people with ASD, they might be able to adequately meet their limited but still present wish for interacting with others, thereby preventing or alleviating feelings of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Since longer term follow-up data are often lacking, the authors of recent meta-analyses could not draw conclusions regarding the long-term effects [ 1 , 2 ]. For studies with 3 months follow-up assessments for treated and non-treated groups, the outcomes varied: the immediate effect of group-based SST reported by Soorya et al [ 5 ] did not sustain at 3 months’ follow-up, whereas Freitag et al [ 6 ] and Deckers et al [ 7 ] reported a significant effect at 3 months’ follow-up. Choque Olsson et al [ 8 ] did not find an effect of training on children, and the effect found for adolescents was shown immediately post treatment only, and not at 3 months follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Общим для всех трех изученных нами исследований было участие в экспериментах родителей. Натуралистическое исследование в амбулаторном учреждении позволило авторам сделать вывод о способности студентов к обобщению навыков [Deckers et al 2016], тогда как авторы другого исследования на базе школы были в состоянии заключить лишь то, что у студентов появились новые социальные навыки [Laugeson et al 2014]. Все три исследования содержат свидетельства положительного воздействия педагогического вмешательства на поведение детей с ASD.…”
Section: Reducing the Frequency Of Aggressive Behaviors For Students unclassified